Penerapan PLTS 200 WP Pada Rumah Hunian Masyarakat Pedesaan Sebagai Listrik Hybrid - Didik Riyanto; Moh Muhsin; Jawwad Shulton Habiby (SinarFe7, 2022)
This research raises the theme of implementing a 200 wp solar power plant in rural community residential homes as hybrid electricity. The aim of this research is to develop a PLTS system as a renewable energy source in community residential homes in order to reduce the community's dependence on sources of electrical energy generated from the process of using coal as fuel. The method used in this research is designed to adapt to the user's environment, the characteristics of use and the determination of PLTS components. The results of the design and application of PLTS 200 wp as hybrid electricity in residential homes for rural communities PLTS can be applied to meet the demand for electrical energy by 28% so as to reduce the burden on the use of electricity generated by PLN